Psikoedukasi untuk Meningkatkan Dukungan Keluarga pada Pasien TB Paru - Bisepta Prayogi (Journal of Ners and Midwifery, 2015)
Tuberculosis (TB) remains a major global health problem. This leads to poor health among millions of people every year and is now ranked second leading cause of death from infectious disease worldwide, after the Human Immunodeficiency Virus (HIV). The objective of this study was to Analyze the influence of psycoeducation to support the family inan effort to increase support famillies of patients with pulmonary tuberculosis.Methods: This study used quasy experiment pre-post test control group design. Total sample was 32 respondents gotten by purposive sampling, divided into experiment and control group. Data were analyzed by Paired T Test, and Independent T Test with significance value of 0.05. Results: Independent T Test analysis showed there psychoeducation influence family to an increased support famillies (p =0,000) between thetreatment and control groups. Discussion: Psychoeducation can increased family support